Assessment of socio-clinical profile of paediatric TB cases admitted to tertiary health care centre, Odisha, India - Jena, Parsuram; Jena, Dhaneswari; Mahapatra, Dillip Kumar; Dandapat, Uttar Kumar; Jena, Pravati (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis is continued to be a major killer of mankind. Childhood tuberculosis contributes to high mortality due to diagnostic difficulty. Different social factors are responsible for its causation. The objective of the study was to assess the socio clinical factors prevalent among paediatric TB cases admitted to MKCG Medical College. Methods: It was a cross sectional study carried out in the indoor paediatric ward of MKCG medical college. Duration of the study was from August 2016 to July 2017. Study participants were all admitted paediatric cases of age group less than 14 years. Data collected through scientifically designed pretested questionnaires. Results: Total 103 patients were admitted during study period of whom, 54% were male. Their median age was 8 years. They were mostly Hindu by religion (98%) and from lower socioeconomic classes (77%). Majority (60%) were from nuclear family (59%) and families of BPL card holder. Most of their parents had low educational status. Physical overcrowding, inadequate ventilation in the house and smoking were main epidemiological factors observed. Conclusions: It was concluded from the above study group, socioeconomic and environmental risk factors were widely prevalent among them. So, control of these factors are the priority issues to be addressed and improvement of these conditions are recommended for effectiveness of the curative measures.